ANALYSIS OF INTERNAL AUDITOR POSITION AND FUNCTIONS IN THE COMPANY - Nani Rohaeni; Supatmin Supatmin; Dini Martinda Lestari; Noryani Noryani (Yayasan Education and Social Center, 2022)
The implementation of supervision can be carried out directly by the owner himself and can also be carried out through an internal control system. With the company's development, the activities and problems faced by the company are increasingly complex, so it is increasingly difficult for the leadership to carry out direct supervision of all company activities. This research is in the form of literature searches and field research. Library Research was passed by reading literature related to internal auditors. The field research was conducted by examining the roles and functions of the company's internal auditors, namely Company X. The data was done by observation, interviews, literature, and data analysis methods used were descriptive and comparative methods. The research results are (1) the position of the internal auditor in the company's organizational structure is under the president. (2) The implementation of the supervisory function carried out by the Internal Auditor has significantly contributed to the Company's management by knowing how the activities have been carried out. (3) Internal auditors in carrying out their functions independently of the company's routine tasks. (4) The Internal Auditor first prepares an inspection program and work document during the inspection. (5) Each report on the inspection results produced by the internal auditors is submitted to the director for each object of inspection verified. The presence of the internal auditor's report can contribute to the determination of plans and policies